THE AFRICAN PEER REVIEW MECHANISM - Mugeni, Kayitenkore (My University, 2011)
The New Partnership for Africa’s Development (NEPAD) is a vision and a strategic framework aiming to revive Africa’s development. The African Peer Review Mechanism (APRM) is a tool of the NEPAD adhered to on a voluntary basis. APRM is intended to promote democracy and good political governance, economic governance and management, corporate governance and socio-economic development. This study examines the effort of undertaking the African Peer Review Mechanism in Rwanda and its impact on policy development in that country. The study is foremost an attempt to show the Peer Review at work and its potential benefits and shortcomings in Rwanda. Findings derived from the analysis of official documents from NEPAD and expert opinions have demonstrated that by promoting good governance throughout government policies, the APRM does act as an effective and enabling mechanism that will facilitate strategic development policy in Rwanda as good governance leads to sustainable development. Hence it was recommended that Rwanda builds capacity in policy making; civil society organisations should strengthen their structures to effectively play their role of watchdogs; and finally, that monitoring and evaluation mechanisms be implemented to evaluate policy outcomes and provide necessary information for decision making purposes.
MM - P&DM
Keywords: African Peer Review Mechanism; Development, Rwanda; New Partnership for Africa's Development